Optical Soliton Solutions of the Cubic-Quartic Nonlinear Schrodinger and Resonant Nonlinear Schrodinger Equation with the Parabolic Law - Gao, Wei; Ismael, Hajar Farhan; Husien, Ahmad M.; Bulut, Hasan; Baskonus, Haci Mehmet (Mdpi, 2020)
Featured Application The optical soliton solutions obtained in this research paper may be of concern and useful in many fields of science, such as mathematical physics, applied physics, nonlinear science, and engineering. Abstract In this paper, the cubic-quartic nonlinear Schrodinger and resonant nonlinear Schrodinger equation in parabolic law media are investigated to obtain the dark, singular, bright-singular combo and periodic soliton solutions. Two powerful methods, the expansion method are utilized to construct some novel solutions of the governing equations. The obtained optical soliton solutions are presented graphically to clarify their physical parameters. Moreover, to verify the existence solutions, the constraint conditions are utilized.
Keywords: cubic-quartic Schrodinger equation; cubic-quartic resonant Schrodinger equation; parabolic law